Intellectual technologies of entrepreneurship management (Regional aspects of productive forces development of Ukraine, 2020)
Introduction. The article examines the intelligent technologies of business management. It is established that an important factor of successful entrepreneurship is to increase the efficiency of management by optimizing management methods.Goal. The goal of the article is research and development of intelligent technologies of business managementResults.  Leadership has been found to be achieved through unique intangible factors. The system of support of administrative decisions based on flexible response to inquiries of consumer capital is analyzed. The main direction of formation of a new (intellectual) economy is the formation of human capital, its intellectualization, the presence of a component of knowledge and creativity in its activities. The transition to a new level of management is carried out through the integrated development of the management information system, so one of the main conditions for modeling the management system is the process of business intellectualization. Management involves the presence of an entity that controls (the control part of the control system) and an object that is controlled (the controlled part of the control system).The peculiarity of this system, which is to provide the necessary information for management decisions, is revealed. Process, system and situational approaches to management, which provide a set of continuous series of situational management functions performed in the business entity, are highlighted. Entrepreneurs who invest in the development of IT-technologies are largely interested not in the mathematical correctness or reliability of the results, but in the practical significance of the conclusions.A process control scheme has been formed, where a step-by-step solution of a number of problems is required. It is stated that the system is an ordered set of related, interacting elements or parts, united into a single whole and functioning to achieve a strategic goal. The main task of the control system is to ensure optimal (rational) functioning of the control object (transfer it to the target state). Optimality is ensured by the correct choice of the goal, ways to achieve it and the technology of movement to the goal (sequence of tasks) with the existing limitations on resources.